Carbon Nanofiber and Meldola Blue Based Electrochemical Sensor for NADH: Application to the Detection of Benzaldehyde. Issue 11 (17th September 2018) - Titoiu, Ana Maria; Lapauw, Maxime; Necula‐Petrareanu, Georgiana; Purcarea, Cristina; Fanjul‐Bolado, Pablo; Marty, Jean‐Louis; Vasilescu, Alina
Abstract: Nanomaterials used in tandem with electrochemical mediators on screen‐printed electrodes enable sensitive, low cost detection of NADH with minimal interferences in real‐world samples. In this work we investigated the combination between the mediator Meldola Blue and several types of commercial screen‐printed carbon electrodes, i. e. modified with mesoporous carbon, single wall carbon nanotubes, graphene or carbon nanofibers (CNF) as NADH detectors. The sensors were compared with bare carbon electrodes and with commercially available Meldola Blue‐modified electrodes. The best sensitivity for NADH detection by amperometry was observed for Meldola Blue/CNF electrodes, and further improvement was obtained by mixing the mediator with graphene oxide prior to dropcasting. The "MB‐erGO/CNF" sensors obtained were characterized by a detection limit of 0.5 μM, a linear range of 1–300 μM and a sensitivity of 80.0±2.5 μA cm −2 mmol −1 L, 10 times higher than that of commercial sensors. While the use of graphene oxide lead to enhanced sensitivity and wider linear range, it didn't improve the operational stability as the mediator gradually desorbed from the electrodes. Furthermore, the sensors were coupled with a new NAD + ‐dependent aldehyde dehydrogenase from a psychrophilic bacterium for the analysis of benzaldehyde and proven to be advantageous over commercial electrodes with Meldola Blue in circumstances where the detection was limited by NADH detection, i. e. at pH 9.5. Abstract :